Failure of Flow Diverter Therapy: Predictors and Management Strategies. (16th December 2019) - Bonney, Phillip A; Connor, Michelle; Fujii, Tatsuhiro; Singh, Parampreet; Koch, Matthew J; Stapleton, Christopher J; Mack, William J; Walcott, Brian P
Abstract: Flow diversion is a safe and effective treatment for many types of brain aneurysms. Even so, there remain some aneurysms that persist despite initial treatment. In studies with the longest follow-up (5 yr), at least 5% of aneurysms persist with this treatment modality. As the cumulative experience and clinical indications for flow diversion continue to expand, the anatomic and functional characteristics that are associated with aneurysm persistence are increasingly described. Identification of these factors preoperatively can help to guide initial treatment decisions, enhance monitoring protocols in the follow-up period, and establish best practices for re-treatment when necessary. Herein, we review published clinical series and provide examples to highlight variables implicated in aneurysm persistence after treatment with flow diversion.